Hubungan Self Efficacy dengan Self Management Pada Pasien Post Stroke - Fransiska Anita Ekawati Rahayu Sa’pang; Elmiana Bongga Linggi; Trysna Levia Kulla; Zyatna Patattan (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Stroke is a circulatory disorder in the brain that occurs suddenly, which is characterized by loss of function from certain parts of the body so that it is disabled. Strokes that enter the rehabilitation phase to reduce disability cause body functions to increase so that they can carry out daily activities that are part of self-management. So that it will be able to self-efficacy well so that self-management in the rehabilitation phase can run. Aims: To know the relationship between self-efficacy and self-management in post-stroke patients. Method: This type of research is observational analytic with a cross-sectional study research design. Sampling using non-probability sampling techniques through accidental sampling amounted to 41 respondents. The instrument used is a questionnaire. Results: Statistical trials showed that there was an association between self-efficacy with self-management in post-stroke patients. Conclusion: That has implications for nurses the importance of increasing self-efficacy in stroke patients so that patients are motivated to heal and improve their quality of life and have an impact on good self-management